Rancang Bangun Sistem Informasi Stok Barang Berbasis Website - Zuriati, Zuriati (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
The arrangement of the stock of goods is a vital component in the trading business, because the availability of goods owned by the number of goods that come out is recorded. This recording is one part of the stock inventory component. A stock of goods is said to be balanced if, incoming goods, outgoing goods and the rest of the goods have a total amount equal to the total number of goods at the time of entry into the warehouse. The main component of other than recording is the flow of goods turnover has a clear track record. The use of information systems can easily keep track records of per unit of goods. This study takes a case regarding the stock of goods at a smartphone shop, the flow of the goods turnover process at the store is unique from other stores, because every day goods or units of goods must be circulated. From these problems, an Inventory System for Web-Based Mobileshops was built, there are several steps of data flow to describe the flow of information and transformations that are applied when data moves from input to output, namely, Event List, Data Flow Diagram, CDM, PDM, and Design. The system user interface is built. PHP and MySQL programming languages ​​are used to build the System. Based on the BlackBox testing carried out, it can be concluded that the Inventory System Design for Web-Based Mobileshop has been successfully built. The features of this system are managing loan application data, managing brand data, cellphones, outgoing goods and incoming goods as well as managing DO and producing output reports of goods going out and goods coming in.